(untitled) (Samarra Journal of Pure and Applied Science, 2026)
Obesity is a medical condition defined as the disproportionate storage of excessive body fat، which can negatively impact health.This study was conducted to estimate the levels of obestatin، adipsin، and neuropeptides، as well as glutathione and malondialdehyde،and biochemical variables، including lipids and sugar . study was conducted on obese males. Samples totaling 90 were collected from Samarra city،( Al-Qala’a، and Al-Huwaish). The samples were divided into groups according to body mass index into a control group and overweight and obese groups for males aged 25-45 years، during a period from August 14، 2024، to September 30، 2024.The results showed an increase in the body mass index with overweight and obesity، which reached 28.12±0.91 and 34.64±2.83 kg/m2، respectively، compared to the control group (22.70±0.97). A significant decrease in the levels of obestatin and glutathione ، at (P ≤0.05) of overweight individuals، as they were lower in obese individuals compared to healthy individuals. Meanwhile، adipsin، neuropeptide، and malondialdehyde increased in overweight and obese patients compared to the healthy group at a probability level of (P ≤0.05). Conclusion: This study conclude that the levels of obestatin، glutathione، and high-density lipoprotein cholesterol decreased in overweight and obese men compared to healthy individuals. In healthy individuals. Levels of adipsin، neuropeptide A، total cholesterol ،triacylglycerol، low density lipoprotein، very low density lipoprotein ، glucose، and malondialdehyde were elevated in overweight and obese men compared to healthy individuals.